5-Azacytidine and Resveratrol Enhance Chondrogenic Differentiation of Metabolic Syndrome-Derived Mesenchymal Stem Cells by Modulating Autophagy. (12th May 2019) - Marycz, K.; Houston, J. M. Irwin; Weiss, C.; Röcken, M.; Kornicka, K.
Abstract : Recently, metabolic syndrome (MS) has gained attention in human and animal metabolic medicine. Insulin resistance, inflammation, hyperleptinemia, and hyperinsulinemia are critical to its definition. MS is a complex cluster of metabolic risk factors that together exert a wide range of effects on multiple organs, tissues, and cells in the body. Adipose stem cells (ASCs) are multipotent stem cell population residing within the adipose tissue that is inflamed during MS. Studies have indicated that these cells lose their stemness and multipotency during MS, which strongly reduces their therapeutic potential. They suffer from oxidative stress, apoptosis, and mitochondrial deterioration. Thus, the aim of this study was to rejuvenate these cells in vitro in order to improve their chondrogenic differentiation effectiveness. Pharmacotherapy of ASCs was based on resveratrol and 5-azacytidine pretreatment. We evaluated whether those substances are able to reverse aged phenotype of metabolic syndrome-derived ASCs and improve their chondrogenic differentiation at its early stage using immunofluorescence, transmission and scanning electron microscopy, real-time PCR, and flow cytometry. Obtained results indicated that 5-azacytidine and resveratrol modulated mitochondrial dynamics, autophagy, and ER stress, leading to the enhancement of chondrogenesis in metabolically impaired ASCs. Therefore, pretreatment of these cells with 5-azacytidine and resveratrol may become a necessary intervention before clinical application of these cells in order to strengthen their multipotency and therapeutic potential.